Effect of Superabsorbent Polymer (SAP) Internal Curing Agent on Carbonation Resistance and Hydration Performance of Cement Concrete - Jieting Xu; Xiao Qin; Zhenying Huang; Yongkang Lin; Ben Li; Zhengzhuan Xie (Advances in Materials Science and Engineering)
To clarify the influencing mechanism of superabsorbent polymer (SAP) internal curing agent on the carbonation resistance of cement concrete, accelerated carbonation experiment was conducted to explore the effect of particle size and dosage of SAP on carbonation depth. The hydration performance of internally cured concrete at different ages was studied by Fourier transform infrared spectroscopy (FTIR) test and X-ray diffraction (XRD) test. Combined with the scanning electron microscope (SEM) test, the hydration filling effect of internal curing on the microstructure of concrete was analyzed; meanwhile, the influence mechanism of SAP on carbonation resistance was revealed. The results showed that (i) when the particle size and dosage of SAP were 100 mesh and 0.200%, the carbonation depth of internally cured concrete was only 56.5% of the control group on day 28; (ii) the Ca(OH)2 absorption peak area of SAP-concrete in the FTIR spectra could be increased by 3.38 times than that of the control group, and more C2S and C3S were translated into Ca(OH)2, which helped to improve the hydration degree of cement concrete; (iii) the hydration products of day 56 were increased significantly and the remaining pores formed by SAP gels were gradually filled by hydration products, which enhanced the compactness and carbonation resistance of cement concrete.